SISTEM INFORMASI PERPUSTAKAAN E-LIBRARY STMIK ASIA MALANG BERBASIS JAVA SERVER PAGE - ., Setyorini; Almu’iini Adha, Fadhli (JURNAL TEKNOLOGI INFORMASI: Teori, Konsep, dan Implementasi, 2017)
The development of library services, especially in University is not be separated from the addition of system-based services online or through the assistance of the Internet network, commonly called the online library. Many ways in which transactions are carried out in order to attract visitors read perpusktakaan and provide ease of library services. Starting from beautify the library website page views, view the catalog online book inventory to enjoy libraries of books no longer have to be physical book but also provide e-book and journal thesis conducted at the college. Libraries in creating a website online is not only quite superior in the layout and design of the website only. But which should also be considered is the level of security of the website. To mengjhasilkan online library website is user friendly and secure from the threat of cyber crime, the researchers in this study memenggunakan Java Server Page as a web server. Keywords: Online Library, User Friendly, Java Server Page